Aetiopathogenesis of sandcrack in cattle and its treatment. Issue 2 (21st May 2013) - Murray, Richard D; Williams, Helen J; Bardell, David A
<x xml:space="preserve">Abstract</x> Sandcrack is the most acutely painful claw horn defect that affects dairy and beef cattle. It is the most common lesion associated with cattle lameness that is referred by practising veterinary surgeons to the University of Liverpool's Farm Animal Hospital. The key to its successful treatment is excellent restraint and analgesia that enables precise surgical removal of all under‐run and abnormal growing horn from surrounding necrotic laminae and corium.